PENERAPAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN ANALISIS DAN SINTESIS MAHASISISWA PADA MATA KULIAH KAJIAN KURIKULUM DAN BUKU TEKS - Sumiyatun Septianingsih; Ipong Jazimah (Khazanah Pendidikan, 2020)
ABSTRACTThis study aimed to (1) reveal the increase in analysis and synthesis of studentsthrough the implementation of cooperative learning approaches with the Problem BasedLearning (PBL) method, (2) find out the learning problems experienced by students andtheir solutions. This research was conducted with the stages similar to classroom actionresearch consisting of: (1) action planning (plan), (2) implementing the action (do) and(3) observation and reflection (see). The subjects of the research in this study were thefourth semester students of History Education Study Program in the academic year2018/2019, as many as 26 students. This research was conducted in February-June2019. The subject taken in this study was A Study of Curriculum and Textbooks. Datacollection techniques were done by interview, observation and literature study.Triangulation was employed to validate the data, namely, (1) source or datatriangulation, (2) method triangulation, and (3) theory triangulation. The data obtainedwere then analyzed using qualitative descriptive through four stages, consisting of; datacollection, data reduction, data presentation and drawing conclusions or verification.The results of this study indicated that in the first cycle the average of synthesis analysisthinking ability in the group category was 61.1% in the fair category and 38.9% in thegood category, in the second cycleit increased to 50% in the good category and 50%good enough category. In the individual category 50% are in the fair category, 38.5%in the good category and 11.5% in the poor category, while in the second cycle, it raisedto 53.8% in the good category, 34.6% in the fair category, and 11.5% in the poorcategory. Furthermore, in the cycle III the mean of synthesis analysis thinking ability forthe group category was 94.4% in the good category and 5.6% in the fair category. Inthe individual category 65.4% was in the good category and 34.6% was in the faircategory. Based on these results, it could be concluded that the increase of students’synthesis analysis thinking ability in group was quite good, including for individualabilities. The lack of students’ interest in reading became a major factor in otherresearch findings.Keywords: Problem Based Learning (PBL), lesson study, analytical and synthesis